Medications for Allergic Rhinitis: An Opportunity for Quality Improvement?. (January 2017) - Roditi, Rachel E.; Ishman, Stacey; Lee, Stella; Lin, Sandra; Shin, Jennifer J.
Objectives: Adherence to the allergic rhinitis clinical practice guideline is being considered as a potential focus for national performance metrics. To help inform this discussion, we assessed patient- and clinician-reported medication administration among nationally representative populations of patients with allergic rhinitis. Study Design: Cross-sectional analyses. Setting and Subjects: Home health assessments, ambulatory visits. Methods: Participants in the National Health and Nutrition Examination Survey and the National Ambulatory Medical Care Survey / National Hospital Ambulatory Medical Care Survey were assessed. The primary outcomes were the percentage of patients reporting receipt of antihistamines and/or nasal steroids among those with allergy-related symptoms and the percentage for whom a clinician administered these medications when diagnosing allergic rhinitis. Secondary outcomes included assessments of those with worse quality of life, confirmatory allergy testing, and leukotriene receptor antagonist use. Results: Within the National Health and Nutrition Examination Survey, an estimated 29.2 million patients were diagnosed with "hay fever, " while 92.2 million were diagnosed with "allergies." Patients with symptoms of allergic rhinitis reported that antihistamines or nasal steroids were prescribed in 21.1% to 24.0% of cases. Leukotriene receptor antagonists were given to 1.7% of those without asthma or use of other allergy medications. Within the National Ambulatory Medical Care Survey / National Hospital Ambulatory Medical Care Survey, observations representing 149.5 million visits for allergic rhinitis demonstrated that nasal steroids were administered in 29.6% of cases, while nonsedating and sedating antihistamines were given in 22.4% and 17.2%, respectively. Conclusions: Despite a high prevalence of allergic rhinitis, per patient report and clinician entry, a substantial number of affected patients do not receive antihistamines and nasal steroids.